Analytical approximations and decision-making techniques for power systems under uncertainty - Pareek, Parikshit (Nanyang Technological University, 2023)
The integration of distributed energy resources and increasing adoption of electric vehicles continue to drive uncertainty in power systems to an unprecedented level. In view of reduced applicability of traditional analysis and decision-making methods, this dissertation aims to address the need for new approaches, by attempting to solve three different sets of problems.